ENHANCING THE EFFICIENCY OF INDOOR LOCAL VENTILATION USING CROSS-FLOW FANS: CASE STUDY FOR A SMOKING CABIN - ANDREI DRAGOMIRESCU; ADRIAN CIOCĂNEA (Journal of Engineering Studies and Research)
The paper presents an original solution for increasing air quality and reducing energy consumption of the local indoor ventilation by using cross-flow fans. The solution is a combination between the local exhaust ventilation (LEV) technique from industry, negative-pressure isolation rooms used in hospitals, and air curtains (AC) used for isolating of indoor/outdoor spaces. The solution provides a high air flow rate at low velocity due to the high value of the flow coefficient of the cross flow fans and, in the same time, allows modular setup according to local space geometry. A case study is proposed regarding the isolation of a smoking area where smell and airborne particles appear. A 3D numerical simulation was performed, in which one cross-flow fan with long axial length was considered. The optimum air flow rate and flow pattern was obtained in order to isolate the local space. The results show that a new approach for reducing sick building syndrome could be addressed by providing modular and local ventilation using cross-flow fans.